THE INFLUENCE OF DHIKR ON STUDENTS' EMOTIONAL INTELLIGENCE - Diva Rania Azzahra; Fatima Hannani Rambe; Putri Maharani; Renda Trinanda Nurbaiti (CV. Doki Course and Training, 2023)
Emotional intelligence is a person's ability to motivate oneself, control feelings of frustration, not be lulled by pleasure, control impulses, be able to manage so that stress does not paralyze the ability to think, and empathize. This study aims to provide an overview of emotional intelligence in students of by providing interventions in the form of dhikr therapy. The subjects of this study consisted of 30 students of . This research method is experimental research with pre-test, post-test, and follow up in one group. Based on output table “Paired Sample Test